Comparative analysis of ABCB1 reveals novel structural and functional conservation between monocots and dicots - Dhaliwal, Amandeep K.; Mohan, Amita; Gill, Kulvinder S. (Frontiers in Plant Science, 2014)
Phytohormone auxin plays a critical role in modulating plant architecture by creating a gradient regulated via its transporters such as ATP-binding cassette (ABC) B1. Except for Arabidopsis and maize, where it was shown to interrupt auxin transport, ABCB1’s presence, structure and function in crop species is not known. Here we describe the structural and putative functional organization of ABCB1 among monocots relative to that of dicots. Identified from various plant species following specific and stringent criteria, ZmABCB1’s ‘true’ orthologs sequence identity ranged from 56-90% at the DNA and 75-91% at the predicted amino acid (aa) level. Relative to ZmABCB1, the size of genomic copies ranged from -27 to +1.5% and aa from -7.7 to +0.6%. With the average gene size being similar (5.8 kb in monocots and 5.7 kb in dicots), dicots have about triple the number of introns with an average size of 194 bp (total 1743 bp) compared to 556 bp (total 1667 bp) in monocots. The intron-exon junctions across species were however conserved. N-termini of the predicted proteins were highly variable: in monocots due to mismatches and small deletions of 1-13 aa compared to large, species-specific deletions of up to 77 aa in dicots. The species- family-, and group- specific conserved motifs were identified in the N-terminus and linker regions of protein, possibly responsible for the specific functions. The near-identical conserved motifs of Nucleotide Binding Domains (NBDs) in two halves of the protein showed subtle aa changes possibly favoring ATP binding to the N-terminus. Predicted 3-D protein structures showed remarkable similarity with each other and for the residues involved in auxin binding.